Experimental investigation on the melting and solidification behavior of erythritol in a horizontal shell and multi-finned tube latent heat storage unit. (October 2019) - Anish, R.; Mariappan, V.; Mastani Joybari, Mahmood
Highlights: Investigated the phase change of erythritol in a horizontal shell-and-multi-finned-tube unit. Experimented thermal response of the system at various operating conditions. Observed higher impact of heat transfer fluid inlet temperature than its flow rate. Achieved promising system thermal performance with no subcooling during solidification. Abstract: Renewable energy sources are incapable of supplying continuous power due to their intermittent availability. To tackle this, energy storage systems incorporating phase change materials can be utilized. Among the several techniques, shell-and-finned-tube configurations show promising heat transfer performance and have greater engineering applicability. This study experimentally investigated the heat transfer mechanism in a horizontal shell-and-multi-finned-tube energy storage unit. Variation of average temperature and storage effectiveness as well as effects of inlet heat transfer fluid temperature and flow rate on the phase change of erythritol were experimentally investigated. It was found that the effect of inlet temperature was more significant than the flow rate (12–32% and 7–17%, respectively). Moreover, natural convection was found to significantly influence the heat transfer during melting where the melted material initially occupied the upper region of the unit and then moved from top to bottom. The outcomes of the present work help understand the effect of natural convection to be effectively utilized for the design and optimization of such storage configurations.